Microcytic hypochromic Anemia is a risk factor for postoperative HAEC: A retrospective study - Huang, Yuanyuan; Ren, Hongxia (Frontiers in Surgery, 2023)
Background Hirschsprung-associated enterocolitis (HAEC) is a common and life-threatening complication of Hirschsprung's disease (HSCR), which can occur before and after surgery. The aim of this study was to identify the risk factors associated with the development of HAEC. Methods We retrospectively reviewed the medical records of HSCR patients admitted to the Children's Hospital of Shanxi Province, China, between January 2011 and August 2021. Diagnosis of HAEC was made using a scoring system with cutoff values ≥4 and included the patient's history, physical examination, and radiological and laboratory findings. The results are shown as frequency (%). The chi-square test was used to analyze a single factor with a significance level of P < 0.05. Logistic regression analysis was used to analyze multiple factors. Results A total of 324 patients were included in this study, with 266 males and 58 females. In total, 34.3% (111/324) of patients had HAEC, including 85 males and 26 females; 18.9% (61/324) of patients had preoperative HAEC; and 15.4% (50/324) of patients had postoperative HAEC within one year after surgery. Gender, age at definitive therapy, and feeding methods were not found to be associated with preoperative HAEC in univariate analysis. Respiratory infection was associated with preoperative HAEC (P = 0.00003). No association was found between gender and age at definitive therapy and postoperative HAEC. Postoperative HAEC was associated with microcytic hypochromic anemia (P = 0.00058), preoperative history of HAEC (P = 0.00120), the creation of a preoperative stoma (P = 0.00097), long segment or total colon HSCR (P = 0.00057), and hypoalbuminemia (P = 0.03225). Regression analysis showed that microcytic hypochromic anemia (OR=2.716, 95% CI = 1.418–5.203, P = 0.003), preoperative history of HAEC (OR=2.814, 95% CI = 1.429–5.542, P = 0.003), the creation of a preoperative stoma (OR=2.332, 95% CI = 1.003–5.420, P = 0.049), and long segment or total colon HSCR (OR=2.167, 95% CI = 1.054–4.456, P = 0.035) were associated with postoperative HAEC. Conclusion This study revealed that the incidence of preoperative HAEC at our hospital was associated with respiratory infections. In addition, microcytic hypochromic anemia, preoperative history of HAEC, the creation of a preoperative stoma, and long segment or total colon HSCR were risk factors of postoperative HAEC. The most important finding of this study was that microcytic hypochromic anemia was a risk factor for postoperative HAEC, which has been rarely reported. Further studies with larger sample sizes are necessary to confirm these findings.